Synthesis, computational pharmacokinetics report, admet study and molecular docking of new thiosemicarbazones potential inhibitors of her2 - positive breast cancer [Articol] - Rusnac, Roman; Ciursin, Andrei; Gulea, Aurelian (CEP USM, 2024)
To maintain a high level of healthcare, humanity needs to develop new drugs. Thiosemicarbazones represent a very interesting class of substances from the point of view of their biological activities. Despite this, their use is very limited due to their toxicity. To solve this problem, it is possible to synthesize thiosemicarbazones based on natural substances. This can reduce their toxicity without loss of eﬀectiveness. a number of computational methods can be used for the design and preliminary evaluation of thiosemicarbazones, which will help eliminate many unsuitable candidates. This will help reduce the cost and speed up the pace of development of new eﬀective substances from this class. such methods include aDMeT calculations and molecular docking.

Pentru a menține un nivel ridicat de asistență medicală, omenirea trebuie să dezvolte în permanență noi medicamente. Tiosemicarbazonele reprezintă o clasă foarte interesantă de substanțe din punct de vedere al gamei de activități biologice. În ciuda acestui fapt, utilizarea lor este foarte limitată din cauza toxicității lor. Pentru a rezolva această problemă, este posibil să se sintetizeze tiosemicarbazone pe bază de substanțe naturale. acest lucru le poate reduce toxicitatea fără pierderea eficacității. O serie de metode de calcul pot fi utilizate pentru proiectarea și evaluarea preliminară a tiosemicarbazonelor, ceea ce va ajuta la eliminarea unor candidați nepotriviți. acest lucru va ajuta la reducerea costurilor și la accelerarea ritmului de dezvoltare a noilor substanțe eficiente din această clasă. astfel de metode includ calcule aDMeT și andocare moleculară.
Sinteză, farmacocinetică computațională, studiu admet și andoarea moleculară (docking) a noilor tiosemicarbazone inhibitori potențiali ai cancerului de sân her2
Keywords: Thiosemicarbazones; anticancer; HER2; molecular docking; ADMET; tiosemicarbazone; anticancer; HeR2; andocare moleculară; aDMeT